Revival and Regeneration of Long-Term Dormant Phalaenopsis amabilis (L.) Blume Protocorms Using PLB Techniques: A Cost-Effective Strategy for Orchid Germplasm Conservation (Early view) - Simaa Ramziyah binti Mohd Yazid, Alvera Elka Meyrick, Eyen Khoo; Richard J. Majapun (Tropical Life Sciences Research, 2026)
Phalaenopsis amabilis, a highly valued orchid native to tropical Asia, is a key component of the global orchid trade. However, increasing demand and unregulated collection have placed considerable pressure on wild populations. Tissue culture is widely used for conservation and propagation, but long-term in vitro cultures often become dormant due to irregular maintenance, leaving valuable germplasm inactive. This study aimed to develop a revival protocol using Protocorm-Like Body (PLB) techniques to regenerate decade-old dormant cultures of P. amabilis, and to evaluate this approach as a technically viable and cost-effective conservation strategy for other rare, high-value orchid species as an alternative to seed banking or cryopreservation. Results showed that dormant PLBs cultured on ½ MS medium exhibited the fastest regeneration, with shoot and root formation observed as early as week 4. This medium also achieved the highest regeneration rate (40%) and survival rate (60%), together with an average of 1.45 ± 2.28 shoots and 0.8 ± 1.51 roots per explant. The superior performance of ½ MS suggests that a reduced-nutrient environment supports the gradual reactivation of metabolic activity, promoting regeneration and survival in dormant cultures. Additionally, MS medium supplemented with 20 g/L coconut powder enhanced protocorm proliferation, producing the highest mean number of secondary PLBs (7.8±10.81). These findings highlight the value of simple, low-nutrient media in reviving long-term dormant orchid cultures and provide a potential protocol for ex situ conservation of P. amabilis and related species.